Diabetes não controlado e trajetória de declínio da função cognitiva: há diferenças entre homens e mulheres e nos domínios afetados? - Cochar-Soares, Natália (2022)
Background: Despite the high prevalence of type 2 diabetes mellitus and its consequent complications, there is still a lack of longitudinal studies that analyze the cognitive decline considering disease uncontrolled cases. Objective: To analyze the trajectory of cognitive function, in analyzes stratified by sex, according to the presence and control of diabetes during eight years of follow-up. Method: Data from 3,984 participants from English Longitudinal Study of Ageing (ELSA Study) were used, 1,752 men and 2,232 women. The study outcomes were the performance of cognitive domains memory, executive function, temporal orientation, in addition the global cognition. Cognitive performance in each test was standardized as z-score by schooling and age. Exposure was classified into participants without diabetes, with controlled diabetes and with uncontrolled diabetes. For the trajectory analyzes of the global cognition and cognitive domains, generalized linear mixed models were used for men and women, separately, and controlled by sociodemographic, behavioral and health conditions variables. Inverse Probability Weighting (IPW) was used to compensate losses of follow-up and to correct survival bias, common in longitudinal studies. Results: No differences were found between the z-score of global cognition and cognitive domains according to baseline diabetes status in either men or women. During eight years of follow-up, women with uncontrolled diabetes had a greater decline in global cognition z-scores - 0.037 sd per year (95%CI - 0.073; - 0.001) and executive function - 0.049 sd per year (95% CI - 0.092; - 0.007) when compared to those who did not have diabetes. There was no difference in the trajectories of the memory and temporal orientation cognitive domains as a function of diabetes status in women. In men, there was no difference in global cognition trajectories as well as in any cognitive domains according to diabetes status. Conclusion: Women who do not control adequately the blood glucose have a greater risk of cognitive decline. Global cognition and the executive function domain seem to be more affected by uncontrolled diabetes than the memory and temporal orientation domains. Gender seems to influence this relationship, since among men there was no association in the trajectory of cognitive function according to diabetes status. Thus, glycemic control, especially in women, is essential for maintaining cognitive function.